Harmonic Analysis in Light Rail Transit Traction - Mohamad Afandi, Nur Alifah (2017)
Traction power system is the main area of industrial sector where the application of power electronic technology is widely used. The uses of these devices create harmonics that cause a serious problem on the proper operation of the system. There have been different corrective methods proposed by different researchers. This thesis provides the harmonic analysis of a traction system. The traction system is modelled using MATLAB/Simulink environment. Simulation is carried out and compared with the IEEE standard limits. Considering the cost and simplicity of operation, a single tuning filter of LC filter is proposed for the DC side of the system. Simulation results greatly reduce harmonic distortion. The simulation result of Total Harmonic Distortion (THD) has been reduced from 14.8% to 1% for voltage, which is far below the 5% limits of IEEE standard.